Method for depositing silver layer on copper alloy complex molded surface

By mechanically polishing, ultrasonic cleaning, organic oil removal, pickling and electrodeposition of silver layers on the complex profile of copper alloy, the problem of poor bonding of copper/titanium bimetallic complex interfaces is solved, and high-quality silver layer electrodeposition and interface connection strength are improved.

CN119553322APending Publication Date: 2025-03-04XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411535746.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The complex copper/titanium bimetallic interface has problems such as violent reactions, excessive brittle interface phase generation, and poor interface combination, which limits its application prospects.

Method used

By mechanically polishing, ultrasonic cleaning, organic oil removal, pickling and electrodeposition of silver layers on the complex surface of the copper alloy, high-quality electrodeposition of silver layers with uniform and crack-free on the copper alloy is achieved.

Benefits of technology

This method effectively improves the interface connection strength between copper alloy and titanium alloy, reduces the content of intermetallic compounds, improves the interface structure, and meets the requirements of different service environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553322A_ABST
    Figure CN119553322A_ABST
Patent Text Reader

Abstract

The invention discloses a method for depositing a silver layer on a copper alloy complex profile, which specifically comprises the following steps: step 1, mechanically polishing bronze alloy profiles respectively, and then putting the bronze alloy profiles into deionized water and absolute ethyl alcohol for ultrasonic cleaning; 2, the bronze alloy profile treated in the step 1 is subjected to organic oil removal; thirdly, the bronze alloy profile treated in the second step is subjected to acid pickling; and 4, electro-deposition is conducted on the bronze alloy profile subjected to acid pickling activation in the step 3, copper alloy with a deposited silver layer is obtained, and then aftertreatment, drying and storage are conducted. The silver layers are electrically deposited on the outer curved surface of the copper alloy rod and the inner curved surface of the copper alloy pipe, so that uniform and crack-free silver layer electro-deposition on the copper alloy is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloy surface treatment and relates to a method for depositing a silver layer on a complex copper alloy surface. Background Art

[0002] As the requirements for the complexity of the shapes of key components in equipment become increasingly higher and the service environment is relatively harsh, it is urgent to develop complex-shaped copper alloys with stable service performance.

[0003] Copper alloys have good wear resistance and can maintain good wear resistance under high load and high friction conditions; titanium alloys have good comprehensive mechanical properties, good organizational stability, and high high temperature strength, and are an important structural material in the aerospace field. However, when copper / titanium bimetallic surfaces are directly connected, there are problems such as violent reactions, excessive generation of interface brittle phases, and poor interface bonding, which seriously limit the application prospects of copper / titanium complex interface bimetallics.

[0004] Copper alloys also have their own limitations. In order to meet the requirements of actual component service conditions, it is necessary to modify the surface of copper alloys. According to the strengthening method, surface modification can be simply summarized as: 1) Surface hardening technology: surface quenching and surface hardening; 2) Coating-cladding-plating technology: electroplating, chemical plating, ion plating, thermal spraying, laser cladding, vapor deposition, etc.; 3) Surface metallurgy (or alloying) technology: glow plasma penetration, laser surface alloying, etc. There are many surface modification methods mentioned above, but there are generally problems such as insufficient surface adhesion and uneven thickness.

[0005] An Ag layer is electrodeposited on the curved surface of copper. No intermetallic compound is formed between Ag and Cu, and only a low-melting-point eutectic reaction occurs. At the same time, the electrodeposited Ag layer can inhibit the direct contact between Cu and the metal to be connected, which can minimize the thermal expansion mismatch between the two metals during the connection process, effectively improve the connection strength, and avoid the formation of brittle intermetallic compounds.

[0006] In summary, it is necessary to propose a method for depositing a silver layer on complex surfaces of copper alloys in order to improve the service reliability of copper alloys in the above-mentioned fields. Summary of the invention

[0007] The purpose of the invention is to provide a method for depositing a silver layer on a copper alloy complex surface, by which high-quality electroplating of a uniform, crack-free silver layer on the copper alloy is achieved.

[0008] The technical solution adopted by the present invention is a method for depositing a silver layer on a complex copper alloy surface, which specifically comprises the following steps: Step 1, mechanically grinding the bronze alloy profiles, and then ultrasonically cleaning them in deionized water and anhydrous ethanol; Step 2, performing organic degreasing on the bronze alloy profile treated in step 1; Step 3, pickling the bronze alloy profile after being treated in step 2; Step 4, electroplating the bronze alloy profile after pickling and activation in step 3 to obtain a copper alloy with a deposited silver layer, and then post-processing and drying for storage.

[0009] The present invention is also characterized in that: In step 1, the bronze alloy profile is a bronze alloy rod or a bronze alloy tube.

[0010] In step 1, ultrasonic cleaning is performed with deionized water for 10 min to 15 min, and then ultrasonic cleaning is performed with anhydrous ethanol for 10 min to 15 min.

[0011] The specific process of step 2 is: immerse the bronze alloy profile after mechanical grinding and polishing in an acetone solution for ultrasonic cleaning for 5 minutes to 15 minutes, and then perform ultrasonic cleaning in deionized water for 5 minutes to 15 minutes.

[0012] The pickling process in step 3 is: immersing the bronze alloy profile in the pickling solution for 55 to 75 seconds.

[0013] The pickling solution in step 3 includes nitric acid and anhydrous ethanol.

[0014] In step 4, during the electrodeposition process, the electrodeposition solution includes silver nitrate with a concentration of 35-45 g / L, sodium thiosulfate with a concentration of 180-220 g / L, potassium pyrosulfite with a concentration of 35-45 g / L, and boric acid with a concentration of 5-30 g / L.

[0015] In step 4, the process parameters of the electrodeposition silver layer are: the electrodeposition temperature is 20-30° C., the pH value of the electrodeposition solution is 4-6, the current intensity is 0.3-0.7A, and the electrodeposition time is 10-30min.

[0016] In step 4, the specific process of post-treatment is: first ultrasonically clean the sample with deionized water for 1 to 10 minutes, then ultrasonically clean the sample with acetone solution for 1 to 5 minutes, and finally ultrasonically clean the sample with anhydrous ethanol for 1 to 5 minutes. After cleaning, the sample is sealed and stored in a vacuum.

[0017] The beneficial effect of the present invention is that the present invention provides a process for electroplating a silver layer on the surface of a copper alloy without pre-deposition and with good bonding effect. On the one hand, no intermetallic compound is formed between silver and copper, and only a low-melting-point eutectic reaction occurs; the types of metal compounds generated by silver and titanium are relatively small and the conditions are complex. On the other hand, silver, as a deposited metal, can effectively block the diffusion of elements such as Al and Fe in aluminum bronze and Zn and Pb in lead bronze, form a good barrier layer at the interface, and reduce the content of intermetallic compounds. It can be seen that the deposited silver layer can play a certain beneficial role in the copper alloy, improve the interface structure, thereby achieving an effective interface connection between the copper alloy and the titanium alloy, and the formed multi-element bronze / two-phase titanium alloy bimetal can meet the requirements of different service environments, and the interface bonding strength is relatively high. By electroplating a silver layer on the outer curved surface of a copper alloy rod and the inner curved surface of a copper alloy tube, the limitation that it is difficult to perform surface treatment on the complex curved surface of the copper alloy is broken through, and a uniform, crack-free silver layer of high-quality electroplating is achieved on the copper alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram of the method for depositing a silver layer on a complex copper alloy surface of the present invention; FIG2 (a) is a scanning electron microscope image of the curved surface of the copper alloy rod in Example 1 of the method for depositing a silver layer on a complex copper alloy surface of the present invention; FIG2( b ) is an EDS spectrum analysis diagram of a selected area of ​​a copper alloy profile deposited layer in Example 1 of the method for depositing a silver layer on a copper alloy complex profile of the present invention; Figure 3 is a scanning electron microscope image of the curved surface of the copper alloy profile in Example 2 of the method for depositing a silver layer on a complex copper alloy profile of the present invention; Figure 4 is a scanning electron microscope image of the curved surface of the copper alloy profile in Example 3 of the method for depositing a silver layer on a complex copper alloy profile of the present invention; FIG5 (a) is a scanning electron microscope image of the curved surface of a copper alloy profile in Example 4 of the method for depositing a silver layer on a complex copper alloy profile of the present invention; FIG5( b ) is an EDS spectrum analysis diagram of a selected area of ​​a deposited layer of a copper alloy profile in Example 4 of the method for depositing a silver layer on a complex copper alloy profile of the present invention. DETAILED DESCRIPTION

[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0020] The method for depositing a silver layer on a copper alloy complex surface of the present invention is as follows: Figure 1 As shown, the method sequentially performs mechanical grinding and polishing, organic oil removal, pickling, electrodeposition of silver and post-treatment on the copper alloy profile.

[0021] The method for depositing a silver layer on a copper alloy complex surface of the present invention comprises the following steps: Step 1: Process the bronze alloy profile into a certain size and perform mechanical polishing on it, that is, polish its surface with sandpaper from low to high. In addition, when replacing the next sandpaper, the sample and sandpaper should be rinsed with water to avoid scratches caused by coarse sand particles, and then put them into deionized water and anhydrous ethanol for ultrasonic cleaning; In step 1, the bronze alloy profile is a rod or a tube, the diameter of the cylindrical bronze alloy rod is 20 mm, the height is 25 mm, the outer diameter of the bronze alloy tube is 20 mm, the inner diameter is 18 mm, and the height is 25 mm. The outer diameter of the bronze alloy tube is kept the same diameter. The specific process of cleaning the mechanically polished bronze alloy profile in an ultrasonic cleaner is: ultrasonic cleaning with deionized water for 10 min to 15 min, and then ultrasonic cleaning with anhydrous ethanol for 10 min to 15 min. After cleaning, the organic oil removal in step 2 is performed.

[0022] Step 2, organic degreasing: immerse the mechanically polished bronze alloy profile in an acetone solution for ultrasonic cleaning for 5 min to 15 min, then ultrasonic cleaning in deionized water for 5 min to 15 min, and then perform pickling in step 3 after drying.

[0023] Step 3, pickling: pickling the bronze alloy profile after organic oil removal, and then washing it again to finally obtain the pretreated bronze alloy profile, drying the bronze alloy profile and sealing it in a vacuum for storage, and then performing the electrodeposition in step 4.

[0024] In step 3, the specific process of pickling is: immersing in a mixed pickling solution consisting of 10% by mass nitric acid and 90% by mass anhydrous ethanol for 55 to 75 seconds.

[0025] Pickling can remove oxide and other thin films on the metal surface. At the same time, pits are formed in the micro-areas of the curved surface after pickling to increase the roughness and contact area, which is beneficial to the subsequent deposition of silver.

[0026] Step 4, electrodeposition: Electrodepositing the copper alloy after pickling and activation to obtain a copper alloy with an electrodeposited silver layer, performing post-treatment and drying for storage.

[0027] In step 4, the components of the electrodeposition solution during the electrodeposition process are: 35-45 g / L silver nitrate, 180-220 g / L sodium thiosulfate, 35-45 g / L potassium pyrosulfite, and 5-30 g / L boric acid; The process parameters of the electrodeposition silver layer are: electrodeposition temperature is 20~30℃, pH value of the electrodeposition solution is 4~6, current intensity is 0.3~0.7A, electrodeposition time is 10~30min, and the mechanical arm speed is 30r / min~120r / min.

[0028] The specific process of post-treatment is: ultrasonic cleaning with deionized water for 1~10min - ultrasonic cleaning with acetone solution for 1~5min - ultrasonic cleaning with anhydrous ethanol for 1~5min. After cleaning, the sample is sealed in a vacuum for subsequent characterization.

[0029] The composition selection and process matching mechanism of the electrodeposition liquid are complex. By changing the process conditions such as current intensity, deposition time, deposition liquid composition and deposition liquid temperature, comparing its microstructure and uniformity, clarifying the change law of deposition effect with process conditions, and selecting the optimal electrodeposition silver layer process for subsequent bimetallic connection.

[0030] The components of the deposition solution mainly include main salt, complexing agent, conductive salt, etc. Main salt refers to the metal salt that can deposit a deposition layer on the cathode. The mass concentration of the main salt directly affects the quality of the deposition layer. AgNO3 is the main salt of the electrodeposited silver layer, and the optimal addition amount is 40g / L.

[0031] Complexing agent refers to a compound that can complex metal ions in the solution and form active ligands with them. The increase in the concentration of complexing agent can effectively improve the quality of the deposited layer. When its concentration is too low, the deposited layer is not bright and the deposition effect is poor; when its concentration is too high, it is easy to burn under a larger current density. The thiosulfate electrodeposition silver system solution is the closest to the cyanide electrodeposition silver system. It has the characteristics of simple composition, convenient preparation, stable process, and excellent comprehensive performance of the silver layer. Therefore, the thiosulfate system is selected to prepare the intermediate silver layer by direct current deposition. The thiosulfate electrodeposition silver system solution mainly uses thiosulfate as a complexing agent, and sodium thiosulfate 180~220g / L is selected.

[0032] Conductive salt refers to a substance that can increase the conductivity of the electrodeposition solution. The content of potassium pyrosulfite changes the direction of its chemical reaction and affects the HSO3 in the deposition solution. - and S2O3 2- The content of potassium pyrosulfite affects the quality of the deposited layer. With the increase of potassium pyrosulfite content, the appearance of the deposited layer and the stability of the deposited liquid are improved.

[0033] Silver salt is silver nitrate, and the mass concentration of silver nitrate directly affects the quality of the deposited layer. Boric acid is selected as a pH stabilizer.

[0034] Many independent process conditions such as temperature, pH value and current density among the process parameters will also affect the quality of the deposited layer and the deposition rate.

[0035] The effect of the deposition liquid temperature on the deposition layer is relatively complex. The increase in the temperature of the electrodeposition liquid will increase the deposition rate, improve the conductivity, and increase the cathode limiting current density to compensate for the decrease in concentration polarization, and finally the deposition layer will be finely crystallized. However, when the temperature is too high, the cathode polarization will be reduced, and the crystals will be rough and loose; when the temperature is too low, the electrodeposition liquid is prone to precipitation, and the deposition layer is gray. Here, the operating temperature is selected as room temperature (20℃~30℃).

[0036] The change of pH value of the deposition solution will affect the state of ions in the electrodeposition solution, thus affecting the stability of the deposition solution and the quality of the deposited layer. The pH value must be strictly controlled. Too low pH value will cause hydrogen evolution reaction during the electrodeposition process, affecting the quality of the deposited layer; too high pH value will cause precipitates to be included in the electrodeposition layer.

[0037] In the process of electrodeposition, appropriately increasing the current density can accelerate the nucleation rate and refine the grains. When the current density is too small, the nucleation slows down, making the grains coarse and the deposited layer rough; when the current density is too large, the ions consumed near the cathode cannot be replenished in time, which will cause the H + Discharge causes serious "hydrogen evolution", which leads to poor brightness of the electrodeposited layer, and the appearance of voids, pitting, looseness and burning. Here, the current intensity is 0.3A~0.7A, and the electrodeposition time is 10min~40min.

[0038] The method for depositing a silver layer on a complex surface of a copper alloy of the present invention, by electro-depositing a silver layer on an outer curved surface of a bronze alloy rod or an inner curved surface of a bronze alloy tube, breaks through the limitation that complex curved surfaces of copper alloys are difficult to surface treat, and realizes high-quality electro-deposition of a uniform, crack-free silver layer on the bronze alloy.

[0039] Example 1 The copper alloy with the grade of QAl10-4-4 (hereinafter referred to as QAl10-4-4) was processed into a Φ20mm×25mm cylinder. The plane of QAl10-4-4 was mechanically polished, ultrasonically cleaned in the order of deionized water, anhydrous ethanol, acetone, and deionized water, and then immersed in a mixed pickling solution consisting of 10% by mass nitric acid and 90% by mass ethanol for 55s to obtain the pretreated QAl10-4-4.

[0040] The pretreated QAl10-4-4 was subjected to electrodeposition treatment. The electrodeposition solution included 35 g / L silver nitrate, 180 g / L sodium thiosulfate, 35 g / L potassium pyrosulfite, and 5 g / L boric acid. The specific process parameters were as follows: electrodeposition temperature was 20 °C, pH value of the electrodeposition solution was 4, current intensity was 0.3 A, electrodeposition time was 10 min, and mechanical arm speed was 30 r / min. The obtained QAl10-4-4 surface was observed for microstructure, as shown in Figure 2 (a). The thickness of the silver layer was measured, where D1 = 43.79 μm, D2 = 39.47 μm, and D3 = 41.09 μm. The thickness of the deposited layer was stable at about 40 μm, and the distribution was relatively uniform, and the surface of the silver layer was relatively flat. In order to clarify the actual element content of the deposited layer, the silver layer at the thickness D3 on the QAl10-4-4 surface was measured and analyzed by EDS spectrum analysis. The element content in this area is shown in Table 1. As shown in Figure 2 (b), the deposited layer contains the largest amount of Ag, and there are also small amounts of Fe, Ni, and Cu elements. No brittle intermetallic compounds are generated between the silver layer and the copper alloy.

[0041] To verify the deposition effect, a hard steel scratcher with a sharp edge of 30° was used to draw two parallel lines about 2 mm apart. When drawing two parallel lines, the lines were cut through the deposition layer to the base metal with sufficient pressure. No peeling was found in any part of the coating between the lines, which shows that the deposition effect is good.

[0042] Table 1

[0043] Example 2 QAl10-4-4 was processed into a Φ20mm×25mm cylinder. Its surface was mechanically polished, and ultrasonically cleaned in the order of deionized water, anhydrous ethanol, acetone, and deionized water, and then immersed in a mixed pickling solution consisting of 10% by mass nitric acid and 90% by mass ethanol for 60 s to obtain the pretreated QAl10-4-4.

[0044] The pretreated QAl10-4-4 was electroplated, and the electroplating solution included 40g / L silver nitrate, 200g / L sodium thiosulfate, 40g / L potassium pyrosulfite, and 25g / L boric acid. The specific process parameters were: the electroplating temperature was room temperature 25°C, the pH value of the electroplating solution was 5.8, the current intensity was 0.6A, the electroplating time was 20min, and the mechanical arm speed was 90r / min. The obtained surface was observed for structure, such as Figure 3As shown, the thickness distribution of the electrodeposited silver layer is uneven, where D1=59.76μm, D2=47.52μm, and D3=41.37μm. The surface of the silver layer is relatively smooth, with fewer defects such as cracks and holes. Example 3 Lead bronze ZCuSn10Pb10 was processed into a Φ20mm×25mm cylinder. Its surface was mechanically polished, ultrasonically cleaned in the order of deionized water, anhydrous ethanol, acetone, and deionized water, and then immersed in a mixed pickling solution consisting of 10% by mass nitric acid and 90% by mass ethanol for 75 s to obtain the pretreated ZCuSn10Pb10.

[0045] Electrodeposition was performed on the pretreated ZCuSn10Pb10. The electrodeposition solution contained 45 g / L silver nitrate, 220 g / L sodium thiosulfate, 45 g / L potassium pyrosulfite, and 30 g / L boric acid. The specific process parameters were: electrodeposition temperature of 30°C, pH value of electrodeposition solution of 6, current intensity of 0.7A, electrodeposition time of 30 min, and mechanical arm speed of 120 r / min. The obtained surface was observed for structure, such as Figure 4 As shown, the thickness distribution of the electrodeposited silver layer is relatively uniform, concentrated in the range of 18~20μm, among which D1=19.55μm, D2=18.38μm, D3=18.65μm, and there are local protrusions on the surface of the silver layer. Example 4 Lead bronze ZCuSn10Pb10 was processed into a tube with an outer diameter of 20 mm, an inner diameter of 18 mm, and a height of 25 mm. Its surface was mechanically polished, and ultrasonically cleaned in the order of deionized water, anhydrous ethanol, acetone, and deionized water, and then immersed in a mixed pickling solution consisting of 10% by mass nitric acid and 90% by mass ethanol for 60 s to obtain the pretreated ZCuSn10Pb10.

[0046] The pretreated ZCuSn10Pb10 was electroplated. The electroplating solution included 35 g / L silver nitrate, 180 g / L sodium thiosulfate, 35 g / L potassium pyrosulfite, and 5 g / L boric acid. The specific process parameters were as follows: the electroplating temperature was room temperature 25°C, the pH value of the electroplating solution was 4.8, the current intensity was 0.3A, the electroplating time was 25min, and the mechanical arm speed was 60r / min. The obtained surface was observed for organization. As shown in Figure 5 (a), the thickness of the electroplated silver layer was about 10μm, with D1=10.54μm, D2=13.11μm, and D3=13.25μm. The surface of the silver layer was relatively flat, but there were protrusions in some local areas. In order to clarify the deposition effect and the actual element content of the deposited layer, the selected area EDS energy spectrum analysis was carried out between the silver layers D2 and D3 of the ZCuSn10Pb10 curved surface. The element content in this area is shown in Table 2. As shown in Figure 5 (b), the Ag element content is the highest in the deposited layer, and there are also a small amount of Zn, Pb, and Cu elements. No brittle intermetallic compounds are generated between the silver layer and the copper alloy.

[0047] Use a hardened steel scribing knife with a sharp edge of 30° grinding angle to draw two parallel lines about 2mm apart. When drawing two parallel lines, use enough pressure to cut through the deposited layer to the base metal in one stroke. No peeling was found in most of the coating between the lines, indicating a good deposition effect.

[0048] Table 2

[0049] The method for depositing a silver layer on a complex copper alloy surface of the present invention has the following advantages: on the one hand, the copper alloy has high chemical activity and its surface is very easy to oxidize to form a natural oxide film. The oxide film naturally formed on the surface of the copper alloy can be effectively removed by the present invention, and the surface of the copper alloy can be activated, thus breaking the current application limitations of the copper alloy. On the other hand, the silver layer prepared by the present invention is bright and flat, and evenly distributed, which expands the application of the copper alloy, and also breaks the limitation that the copper alloy curved surface is difficult to surface treat, effectively hinders the direct contact between the titanium alloy and the copper alloy during the later connection, reduces the formation of a brittle intermediate phase, and solves the problem of low connection strength and poor interface bonding of the copper / titanium heterogeneous bimetallic.

Claims

1. A method for depositing a silver layer on a complex copper alloy surface, characterized in that: The specific steps include: Step 1, mechanically grinding the bronze alloy profiles, and then ultrasonically cleaning them in deionized water and anhydrous ethanol; Step 2, performing organic degreasing on the bronze alloy profile treated in step 1; Step 3, pickling the bronze alloy profile after being treated in step 2; Step 4, electroplating the bronze alloy profile after pickling and activation in step 3 to obtain a copper alloy with a deposited silver layer, and then post-processing and drying for storage.

2. The method for depositing a silver layer on a copper alloy complex surface according to claim 1, characterized in that: In step 1, the bronze alloy profile is a bronze alloy rod or a bronze alloy tube.

3. The method for depositing a silver layer on a copper alloy complex surface according to claim 2, characterized in that: In the step 1, ultrasonic cleaning is performed with deionized water for 10 min to 15 min, and then ultrasonic cleaning is performed with anhydrous ethanol for 10 min to 15 min.

4. The method for depositing a silver layer on a copper alloy complex surface according to claim 3, characterized in that: The specific process of step 2 is: immersing the bronze alloy profile after mechanical grinding and polishing in an acetone solution for ultrasonic cleaning for 5 minutes to 15 minutes, and then performing ultrasonic cleaning in deionized water for 5 minutes to 15 minutes.

5. The method for depositing a silver layer on a copper alloy complex surface according to claim 4, characterized in that: The pickling process in step 3 is as follows: immersing the bronze alloy profile in the pickling solution for 55 to 75 seconds.

6. The method for depositing a silver layer on a copper alloy complex surface according to claim 5, characterized in that: The pickling solution in step 3 includes nitric acid and anhydrous ethanol.

7. The method for depositing a silver layer on a copper alloy complex surface according to claim 5, characterized in that: In step 4, during the electrodeposition process, the electrodeposition solution includes silver nitrate with a concentration of 35-45 g / L, sodium thiosulfate with a concentration of 180-220 g / L, potassium pyrosulfite with a concentration of 35-45 g / L, and boric acid with a concentration of 5-30 g / L.

8. The method for depositing a silver layer on a copper alloy complex surface according to claim 7, characterized in that: In step 4, the process parameters of the electrodeposition silver layer are: the electrodeposition temperature is 20-30° C., the pH value of the electrodeposition solution is 4-6, the current intensity is 0.3-0.7A, and the electrodeposition time is 10-30min.

9. The method for depositing a silver layer on a copper alloy complex surface according to claim 8, characterized in that: In step 4, the specific process of post-treatment is: first ultrasonically clean the sample with deionized water for 1 to 10 minutes, then ultrasonically clean the sample with acetone solution for 1 to 5 minutes, and finally ultrasonically clean the sample with anhydrous ethanol for 1 to 5 minutes. After cleaning, the sample is sealed and stored in a vacuum.